2022
DOI: 10.2215/cjn.00360122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music in Reducing Pain during Hemodialysis Access Cannulation

Abstract: Background and objectivesPain during cannulation for vascular access is a considerable problem for patients with kidney disease who are undergoing hemodialysis. We examined whether listening to music can reduce cannulation pain in these patients.Design, setting, participants, & measurementsWe conducted a multicenter, single-blind, crossover, randomized trial of 121 patients who reported pain during cannulation for hemodialysis. We compared participants listening to “Sonata for Two Pianos in D Major, K.448”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…About 20% of patients on hemodialysis have serious pain during cannulation, despite the use of analgesics topically [ 23 ]. About 48% of dialysis people are afraid of the pain associated with the insertion of needles into the fistula.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…About 20% of patients on hemodialysis have serious pain during cannulation, despite the use of analgesics topically [ 23 ]. About 48% of dialysis people are afraid of the pain associated with the insertion of needles into the fistula.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, these individuals usually have pain in the access arm between dialysis regimens [ 26 ]. Pain is one of the main causes of patients’ withdrawal from hemodialysis because they need about 150 hemodialysis regimens per year [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Music has been shown to be a noninvasive, inexpensive, and useful complementary intervention for reducing pain, anxiety, and distress, and improving relaxation in lung cancer patients undergoing chemotherapy (Tang et al, 2021). Other studies have also demonstrated the use of music therapy to improve nausea and pain in patients with breast cancer undergoing chemotherapy, and in hemodialysis patients (Chirico et al, 2020; Inayama et al, 2022). Music therapy is an emerging discipline based on the theory and methods of psychotherapy; it applies a unique method, through various specially designed music behaviors, to help patients eliminate psychological obstacles, and to restore or improve physical and mental health (Brungardt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The recent study by Inayama et al published in this issue of CJASN is an example of such a study (5). This is a rigorous, multicenter, single-blind, crossover randomized trial evaluating the efficacy of music as an adjunct to analgesics in reducing pain in 121 people on hemodialysis who reported pain at least once per week during access cannulation.…”
mentioning
confidence: 99%